Married female nurses a case study on their family and social relationships and coping strategies - Solinap, John Leo D (University of the Philippines in the Visayas, 2006)
This descriptive study aimed to find out the effects of married female nurses' occupation on their family relationship, social relationship, and level of stress. It also aimed to find out the coping strategies that they use. The respondents for the research were seven (7) married female nurses from Iloilo Doctors Hospital, Iloilo City and Ramiro Hospital in Tagbilaran City, Bohol. An in depth, interview guide was used by the respondents to gather information concerned needed for the study. Also, a nursing stress test was also administered to the respondents. It was found out in the study that the occupation of the married female nurses greatly affect their social relationship, and level of stress. Due to the hectic schedule of their work, the respondents spent lesser time with their family. They were also limited in the leisure activities that the engage in. Results showed that majority of the respondents are frequently of extremely stressful at work. In terms of coping, the respondents employed different coping strategies in work related situations and in non-work related situations. The respondents used problem-focused coping in work related situations while for situations outside of work, they used a combination of emotion-focused coping and problem-focused coping.